Aromatic Clusters as Potential Hydrogen Storage Materials - Pal, Ranita; Chattaraj, Pratim Kumar (Frontiers in Energy Research, 2021)
The scientific community is engrossed in the thought of a probable solution to the future energy crisis keeping in mind a better environment-friendly alternative. Although there are many such alternatives, the green hydrogen energy has occupied most of the brilliant minds due to its abundance and numerous production resources. For the advancement of hydrogen economy, Government agencies are funding pertinent research projects. There is an avalanche of molecular systems which are studied by several chemists for storing atomic and molecular hydrogens. The present review on molecular hydrogen storage focuses on all-metal and nonmetal aromatic clusters. In addition to the effect of aromaticity on hydrogen trapping potential of different molecular moieties, the importance of using the conceptual density functional theory based reactivity descriptors is also highlighted. Investigations from our group have been revealing the fact that several aromatic metal clusters, metal doped nonmetal clusters as well as pure nonmetal clusters can serve as potential molecular hydrogen trapping agents. Reported systems include N4Li2, N6Ca2 clusters, Mgn and Can (n = 8 – 10) cage-like moieties, B12N12 clathrate, transition metal doped ethylene complexes, M3+ (M = Li, Na) ions, E3-M2 (E = Be, Mg, Al; M = Li, Na, K) clusters, Li3Al4‒ ions, Li decorated star-like molecules, BxLiy (x = 3 – 6; y = 1, 2), Li-doped annular forms, Li-doped borazine derivatives, C12N12 clusters, (N4C3H)6Li6 and associated 3-D functional material, cucurbiturils, lithium–phosphorus double-helices. Ni bound C12N12 moieties are also reported recently.